Photogrammetry as a tool for integrating archival data in archaeological fieldwork: Examples from the Middle Palaeolithic sites of Combe–Grenal, Le Moustier, and Regourdou. (August 2016) - Discamps, Emmanuel; Muth, Xavier; Gravina, Brad; Lacrampe-Cuyaubère, François; Chadelle, Jean-Pierre; Faivre, Jean-Philippe; Maureille, Bruno
Abstract: In Palaeolithic archaeology, the resumption of fieldwork in previously excavated sites is a common practice, often motivated by the inadequacy of past recovery protocols for modern archaeological studies. Considering that areas open to new excavations are often limited at such sites, new fieldwork should integrate archival data as much as possible in order to combine old and new information. However, correlations between earlier and modern excavations often prove difficult given the absence of detailed spatial information from previous fieldwork. In many cases, the only available documents consist of schematic drawings, imprecise field notes, and a handful of poor-quality photographs. Here we investigate how photogrammetry can be used to extract valuable spatial information from archive photographs. Examples from three Middle Palaeolithic sites in southwestern France (Combe–Grenal, Le Moustier, and Regourdou) show how interactively combining fieldwork with photogrammetry in the analysis of archival documentation can assist decision making during archaeological excavations. Highlights: Correlations between previous and new excavations present important challenges. Photogrammetry using archive photographs allows valuable spatial information to be extracted. Combining fieldwork with archive photogrammetry aids decision making in the field.